(untitled) (International Scientific Journal Alfraganus, 2026)
In this work an existence and uniqueness of solution of non-local boundary value problem with discontinuous matching condition for the loaded parabolic-hyperbolic equation involving the Riemann-Liouville fractional derivative have been investigated. The uniqueness of solution is proved by the method of integral energy and the existence is proved by the method of integral equations.